2017
DOI: 10.1038/s41467-017-02290-w
|View full text |Cite|
|
Sign up to set email alerts
|

Targeted inhibition of STAT/TET1 axis as a therapeutic strategy for acute myeloid leukemia

Abstract: Effective therapy of acute myeloid leukemia (AML) remains an unmet need. DNA methylcytosine dioxygenase Ten-eleven translocation 1 (TET1) is a critical oncoprotein in AML. Through a series of data analysis and drug screening, we identified two compounds (i.e., NSC-311068 and NSC-370284) that selectively suppress TET1 transcription and 5-hydroxymethylcytosine (5hmC) modification, and effectively inhibit cell viability in AML with high expression of TET1 (i.e., TET1-high AML), including AML carrying t(11q23)/MLL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 66 publications
6
38
2
Order By: Relevance
“…However, in some diseased states, the longer TET1 isoform is also expressed, regulated by additional mostly unidentified factors through the distal upstream promoter. This has been shown to include via activation of STAT3 and STAT5, which drive TET1 expression in AML, providing a possible target for treatment (Jiang et al, 2017 ). Expression of the short isoform is also regulated through a distal enhancer which encompasses one of the regions described as an alternative TSSs in ESCs (Sohni et al, 2015 ), and in the gonadotropes this region is protected from methylation by TET2 (Yosefzon et al, 2017 ).…”
Section: Different Mechanisms Of Regulating Tet Expression Give Rise mentioning
confidence: 99%
“…However, in some diseased states, the longer TET1 isoform is also expressed, regulated by additional mostly unidentified factors through the distal upstream promoter. This has been shown to include via activation of STAT3 and STAT5, which drive TET1 expression in AML, providing a possible target for treatment (Jiang et al, 2017 ). Expression of the short isoform is also regulated through a distal enhancer which encompasses one of the regions described as an alternative TSSs in ESCs (Sohni et al, 2015 ), and in the gonadotropes this region is protected from methylation by TET2 (Yosefzon et al, 2017 ).…”
Section: Different Mechanisms Of Regulating Tet Expression Give Rise mentioning
confidence: 99%
“…It has been reported that Tet1 alternative splicing forms have distinct functions [74]. However, the information regarding the Tet1 alternative splicing is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing mechanism leads to several TET1 isoforms, including the full-length canonical and the short transcripts [69][70][71][72][73]. TET1 expression is regulated by very complicated factors including the reprogramming factors such as Oct3/4, Nanog, and Myc [68,70] in early embryos, ESCs and PGCs [69], the transcription factors in the differentiated cells, and STAT3/STAT5 in acute myeloid leukemia (AML) [74].…”
Section: Tet1 and Regulation Of Its Target Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, 19,940 new AML cases are expected to be diagnosed, and 11,180 AML-associated deaths are expected to occur in 2020 ( https://www.seer.cancer.gov/ ). While there have been countless efforts to develop novel therapeutic strategies suited to the treatment of AML, the majority of patients still suffer from poor outcomes, with recent reports estimating a 5-year survival rate of 40% among AML patients 1 , 2 . As such, there is a clear need to better understand the molecular basis for AML in order to expedite the development of more efficacious therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%